Students’ Ability in Writing Procedure Text at Twelfth Grade Student of SMAN 8 Jambi - Sukarton Sukarton; Khidayatul Munawwaroh; Siti Aisyah (Universitas Batanghari Jambi, 2023)
The purpose of this study was to find out the ability of students in grade 12 at SMAN 8 Jambi City in writing procedural texts. A qualitative descriptive method was utilized. The population comprised students XII IPS at SMAN 8 Jambi City of academic study 2022/2023 and the sample consisted of 36 students from class XII IPS 2. Researchers used a research instrument, an essay test with a predetermined theme, namely food. Into discover these findings, tabulation was used to collect data from students' grades to categorize indicators of students written. Following the discovery of the result data, the researcher classified the student's score using the CRA (Criterion-Referenced Assessment) scale. According to the findings of the research, indicators of students' writing abilities, namely goals (83.3325) and materials (90.2775), have excellent an average score. On the other hand,Â the step indicator has into the average good criterion (77.0825). However, the overall average of all indicators is excellent (83.5641). Furthermore, students' ability in writing procedure texts are scores 83.5555 in the highest category. It is indicated that the level of students' ability writing in procedure text is excellent score, and that demonstrated score of writing procedural texts is highest.